Quality of life of adults and elderly people who practice physical activity in a capital city of northeastern Brazil (Research, Society and Development, 2025)
In recent years, concern for quality of life has become a reality, especially for the middle-aged population. This study aims to identify the benefits of physical activity practices on the quality of life of individuals over 40 years old. This is a cross-sectional study conducted in a Brazilian gym. Validated instruments such as WHOQoL-BREF and the Nottingham Health Profile were used. The statistical analysis in this study was based on a variety of statistical methods, including descriptive measures and hypothesis testing. Strength training provided greater mobility (p=0.029) compared to those who did not practice it, in addition to improving physical condition. Furthermore, physical activity showed benefits in the social and psychological domains, improving social relationships, psychological state, and increasing post-workout energy. Thus, regular physical activities positively impact the quality of life of adults and the elderly by promoting physical, mental, and social health. Strength training, Pilates, and water aerobics stand out for their effectiveness in preventing diseases and slowing the effects of aging.